Odpowiedzi

2009-09-12T15:25:24+02:00
-(-2)³:1,6-[¹₃×(-2)-²+⁴₁₀×√6¼]×0,75 = 8:1/6-[⅓*¼+⁴/₁₀*√25/4]*0,75 =
48-¹/₁₂+⁴/₁₀*⁵/₂]*0,75 = [48-¹/₁₂+1]*0,75 = 46 11/12*¾ = 563//12*¾ = 563/13=43 ⁴/₁₃
2009-09-12T15:43:41+02:00
-(-2)³:1,6-[¹₃×(-2)-²+⁴₁₀×√6¼]×0,75 =5-[1/3*1/4+4/10*5/2]*3/4=
=5-[1/12+1]*3/4=5-13/12*3/4=5-13/16=4 3/16
  • Użytkownik Zadane
2009-09-12T16:13:39+02:00
-(-2)³:1,6-[¹₃×(-2)-²+⁴₁₀×√6¼]×0,75=
=-(-8):¹⁶/₁₀-[¹/₃×(½)²+⁴/₁₀×√²⁵/₄]×¾=
=8×¹⁰/₁₆-[¹/₃×¼+⁴/₁₀×⁵/₂]×¾=
=5-(¹/₁₂+1)×¾==5-(1¹/₁₂)×¾=
=5-(¹³/₁₂)×¾=5-³⁹/₄₈=5-¹³/₁₆=
=4¹⁶/₁₆-¹³/₁₆=4³/₁₆